WEBVTT
00:00:02.760 --> 00:00:13.380
Find the solution to the differential equation dπ by dπ‘ is equal to the square root of ππ‘ that satisfies the initial condition π of one is equal to two.
00:00:13.890 --> 00:00:25.950
The question wants us to find a specific solution to the differential equation dπ by dπ‘ is equal to the square root of π times π‘ using the initial condition that π of one is equal to two.
00:00:26.320 --> 00:00:32.700
We can see that our differential equation is almost already the product of a function in π and the product of a function in π‘.
00:00:33.120 --> 00:00:42.050
In fact, by using our laws of exponents, we can see this more clearly. dπ by dπ‘ is equal to the square root of π multiplied by the square root of π‘.
00:00:42.450 --> 00:00:51.000
Since this is a first-order differential equation which can be written as the products of a function in π and a function in π‘, we call this a separable differential equation.
00:00:51.520 --> 00:00:56.710
To solve this, we want to separate our variables π and π‘ onto opposite sides of the equation.
00:00:56.740 --> 00:00:59.950
Weβll start by dividing through by the square root of π.
00:01:00.400 --> 00:01:06.810
This gives us that one divided by the square root of π times dπ by dπ‘ is equal to the square root of π‘.
00:01:07.200 --> 00:01:14.730
Although dπ by dπ‘ is not a fraction, when weβre solving separable differential equations, we can treat it a little bit like a fraction.
00:01:15.120 --> 00:01:22.900
Using this, we get the equivalent statement one divided by the square root of π dπ is equal to the square root of π‘ dπ‘.
00:01:23.490 --> 00:01:26.400
We then want to integrate both sides of this equation.
00:01:26.950 --> 00:01:42.050
We could then evaluate both of these integrals by using the power rule for integration, which tells us if π is not equal to negative one, the integral of π₯ to the πth power with respect to π₯ is equal to π₯ to the power of π plus one divided by π plus one plus a constant of integration π.
00:01:42.110 --> 00:01:45.430
We add one to the exponent and then divide by this new exponent.
00:01:45.930 --> 00:01:56.620
To see why we can do this, we know that one divided by the square root of π is the same as saying π to the power of negative one-half and the square root of π‘ is the same as saying π‘ to the power of one-half.
00:01:57.030 --> 00:02:06.150
To integrate π to the power of negative a half with respect to π, we add one to our exponent and then divide by this new exponent and add a constant of integration we will call π one.
00:02:06.430 --> 00:02:10.720
And we can simplify this since negative a half plus one is just equal to one-half.
00:02:11.040 --> 00:02:16.490
And we can simplify this further since dividing by a fraction is the same as multiplying by the reciprocal.
00:02:16.520 --> 00:02:20.440
So, dividing by one-half is the same as multiplying by two.
00:02:20.850 --> 00:02:23.580
This gives us two π to the power of a half plus π one.
00:02:23.940 --> 00:02:27.420
We then do the same to integrate π‘ to the power of a half with respect to π‘.
00:02:27.420 --> 00:02:30.410
We add one to our exponent and then divide by this new exponent.
00:02:30.680 --> 00:02:33.350
And we add a constant of integration we will call π two.
00:02:33.670 --> 00:02:35.640
We can simplify this expression further.
00:02:35.680 --> 00:02:40.260
We can combine the constants π one and π two into a new constant we will call π.
00:02:40.690 --> 00:02:45.160
We can simplify this further since one-half plus one is just equal to three over two.
00:02:45.550 --> 00:02:51.760
Finally, just as we did before, instead of dividing by three over two, we can multiply by two divided by three.
00:02:52.130 --> 00:02:58.340
So, we now have the equation two π to the power of a half is equal to two-thirds π‘ to the power of three over two plus π.
00:02:58.750 --> 00:03:04.470
And we can actually find the value of π since the question gives us the initial condition π of one is equal to two.
00:03:04.750 --> 00:03:11.030
π is a function of π‘, so this is actually telling us when π‘ is equal to one, π is equal to two.
00:03:11.480 --> 00:03:21.790
Substituting π‘ is equal to one and π is equal to two into our equation gives us two times two to the power of one-half is equal to two-thirds one to the power of three over two plus π.
00:03:22.160 --> 00:03:24.330
We can simplify this expression slightly.
00:03:24.360 --> 00:03:27.690
Two to the power of one-half is the same as saying the square root of two.
00:03:28.090 --> 00:03:31.390
And one to the power of any number is just equal to one.
00:03:31.390 --> 00:03:33.820
So, one to the power of three over two is one.
00:03:34.270 --> 00:03:37.920
So, this gives us that two root two is equal to two-thirds plus π.
00:03:38.250 --> 00:03:45.280
We can then subtract two-thirds from both sides of this equation to see that π is equal to negative two-thirds plus two root two.
00:03:45.770 --> 00:03:55.010
Substituting this value of π into our equation gives us that two root π is equal to two-thirds π‘ to the power of three over two minus two-thirds plus two root two.
00:03:55.280 --> 00:03:56.840
And we could leave our answer like this.
00:03:56.840 --> 00:04:00.100
However, we see that every term shares a factor of two.
00:04:00.130 --> 00:04:01.980
So, we could just divide through by two.
00:04:02.350 --> 00:04:13.700
Dividing both sides of this equation through by two gives us the solution to the differential equation dπ by dπ‘ is equal to the square root of ππ‘, which satisfies the initial condition π of one is equal to two.
00:04:14.040 --> 00:04:21.650
As the square root of π is equal to one-third π‘ to the power of three over two minus one-third plus the square root of two.